2012
DOI: 10.1111/j.1439-0418.2012.01734.x
|View full text |Cite
|
Sign up to set email alerts
|

Age‐ and temperature‐dependent oviposition model of Neoseiulus californicus (McGregor) (Acari: Phytoseiidae) with Tetranychus urticae as prey

Abstract: In this study, we developed an oviposition model of Neoseiulus californicus (McGregor) with Tetranychus urticae Koch as prey. To obtain data for the model, we investigated the longevity, fecundity and survivorship of adult female N. californicus at six constant temperatures (16, 20, 24, 28, 32 and 36°C), 60–70% RH and a photoperiod of 16 : 8 (L : D) h. Longevity (average ± SE) decreased as temperature increased and was longest at 16°C (46.7 ± 5.25 days) and shortest at 36°C (12.8 ± 0.75 days). Adult developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…sulcatus [ 35 ], 24°C for N . californicus [ 40 ], 25°C for R pedestris [ 37 ], T . basalis [ 42 ] and E .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…sulcatus [ 35 ], 24°C for N . californicus [ 40 ], 25°C for R pedestris [ 37 ], T . basalis [ 42 ] and E .…”
Section: Discussionmentioning
confidence: 99%
“…C. sasakii [33], 20.3˚C for R. padi [45], 21˚C for O. sulcatus [35], 24˚C for N. californicus [40], 25˚C for R pedestris [37], T. basalis [42] and E. kuehniella [44], and 25.2˚C for C. medinalis [41]. Parameters, T L and T H , of the fecundity model were estimated as 16.3˚C and 35.2˚C, implying low and high temperature limitation for reproduction, respectively (Table 5).…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Modelling the development of a predator as a function of temperature, offers useful and precise information that is important for optimizing biological control. Moreover, knowledge of the relationship between the development and mortality of N. tenuis as a function of temperature offers valuable information for programming biofactory mass breeding for commercial purposes as has been shown with other natural enemies like Neoseiulus californicus McGregor (Acari: Phytoseiidae) (Kim et al , 2013) and Stethorus punctillum (Coleoptera: Coccinellidae) (Roy et al , 2002).…”
Section: Introductionmentioning
confidence: 99%
“…A population model of natural enemies, such as N. tenuis , could be used to optimize the timing of release and enhance their potential in suppressing important pests. Better knowledge of the population dynamics of both prey and predator would allow the development of an optimal control strategy (Kim et al , 2013). Previous studies have reported the effect of constant temperature on the life cycle parameters of N. tenuis (Sánchez et al , 2009).…”
Section: Introductionmentioning
confidence: 99%